Assessing the impact of a waste incinerator on the environment using the MAIAC-AOD and AERMOD models - Hongthong, Anuttara; Nakapan, Supachai (Frontiers in Environmental Science, 2023)
The distribution and concentration of air pollutants from the infectious waste incineration between 2019 and 2021 were examined in this study utilizing an AERMOD model, including sulfur dioxide (SO2), nitrogen dioxide (NOx), and particulate matter (PM2.5). The MAIAC-AOD value at a 1 km resolution was used to develop a regression model with meteorological information for predicting PM2.5, which was then compared to the concentration from the AERMOD simulation. The following maximum 1-hour, 24-hour, and annual average concentrations all pollutants were discovered in 2019. The distribution of SO2 and NOx in 1-hour was largest in 2020 at 1000 meters to the northwest, with concentrations of 37.68 and 93.99 µg/m 3 , respectively. While the 24-hour concentration of SO2 and NOx was greatest in 2021, with of 3.63 and 8.90 µg/m 3 , respectively, at 720 meters northeast of the stack. The annual concentration of SO2 and NOx was highest in 2019 with 0.56 and 1.36 µg/m 3 , respectively. The highest annual PM2.5 concentration was 0.033 µg/m 3 at 730 meters in the northeast in 2019. The predicted PM2.5 using MAIAC-AOD correlated with the simulated value from AERMOD with R 2 values of 0.7630, 0.7607, and 0.6504, respectively, between 2019 and 2021, which higher close to the stack than outside. As a result, investigations into the distribution of air pollution should benefit from the integration between the air modeling and the satellite information.